Swedish regional development initiatives in a gender perspective: a regional policy programme evaluated against transversal objective - Barbro Widerstedt (European Regional Science Association (ERSA), 2011)
Gender equality has long been a focus in regional development in the European Union. In a Swedish context, the interest has been borne from the fact that rural and sparsely populated areas have a 'women shortage', and that this tendency is accelerating as young women move to cities, while young men stay in the rural areas. Several remedies to this dilemma have been proposed, and one field of analysis stresses the gender-segregated nature of the Swedish labour market and the relative paucity of employment opportunities for women in rural areas. Regional Investment Grants and Regional Development Grants are use to support investment in eligible areas of Sweden, with the objective of bolstering growth, and maintaining a balanced regional development. In addition to the stated main objectives, the investment projects should also address a range of transversal goals - one of which is gender equality and improved employment opportunities for women. Previous studies have noted that there seem to be relatively few regional investment and development grants awarded to female-run firms. This raises the question of whether the rules regulating the grants disproportionally disadvantage female-run firms, and hence is in conflict with the transversal objective of the grant to promote gender equality and provide a more varied labour market. This paper deals with the application and approval of regional investment and regional development grants to female-run firms in Sweden. The main question is whether the rules of eligibility inherently disadvantage female-run firms, and whether there is a difference between male-run firm and female-run firms in the likelihood of applying for the grant. A rule that grants should be awarded in a way that is competitively neutral within a region disadvantages female-led firms, which are more likely to operate on a local market. Given the industry and size of the applying firm, there is no difference in the likelihood that a firm applies for or is awarded a grant between male-led and female-led firms. I also find that these results are somewhat sensitive to the definition of what constitutes a 'female-led' firm.
Keywords: 330